PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA FITRAH ISLAMIC WORLD ACADEMY - Fikri, Farid Misbahul (UNISAN JURNAL, 2025)
This study aims to analyze the influence of transformational leadership and work motivation on teacher performance at Fitrah Islamic World Academy (FIWA) Senior High School. Transformational leadership is a leadership style that emphasizes inspiration, empowerment, and individual development within the organization. Work motivation is a crucial factor in determining the level of dedication and productivity of teachers in carrying out their duties. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to FIWA teachers. The data analysis techniques included instrument validity and reliability tests, descriptive analysis, and multiple linear regression analysis to examine the relationships between transformational leadership, work motivation, and teacher performance. The results show that transformational leadership has a positive and significant effect on teacher performance, contributing 26.9%, while work motivation has a positive and significant effect, contributing 33.5% to teacher performance. Simultaneously, transformational leadership and work motivation contribute 60.4% to teacher performance, with the remaining 39.6% influenced by other variables not examined in this study. These findings underscore the importance of synergy between school leadership and individual internal motivation in creating a quality educational environment. The findings imply that effective implementation of transformational leadership, supported by strategies to enhance teacher motivation, can improve the quality of teaching and learning. Therefore, schools are encouraged to continuously develop leadership styles focused on individual development and establish systems that sustainably foster teacher motivation.